Effects of statins beyond lipid-lowering agents in ART-treated HIV infection - Mehraj, Vikram; Chen, Jun; Routy, Jean-Pierre (Frontiers in Immunology, 2024)
Antiretroviral therapies (ART) have reduced human immunodeficiency virus (HIV) infectionassociated morbidity and mortality improving the life of people with HIV (PWH). However, ART lead to residual HIV production, which in conjunction with microbial translocation and immune dysfunction contributes to chronic inflammation and immune activation. People living with HIV (PWH) on ART remain at an increased risk for cardiovascular diseases (CVDs) including myocardial infarction and stroke; which in part is explained by chronic inflammation and immune activation. Lifestyle factors and certain ART are associated with dyslipidemia characterized by an increase of low-density lipoprotein (LDL), which further contributes in the increased risk for CVDs. Lipidlowering agents like statins are emerging as immune modulators in decreasing inflammation in a variety of conditions including HIV. The international randomized clinical trial REPRIEVE has shed light on the reduction of CVDs with statin therapy among PWH. Such reports indicate a more than expected benefit of statins beyond their lipid-lowering effects. Bempedoic acid, a first-in-class nonstatin LDL-lowering drug with immuno-modulatory effects, may further aid PWH in combination with statins. Herein, we critically reviewed studies aimed at lipid-lowering and immune-modulating roles of statins that may benefit aging PWH.